Examining the day-level impact of physical activity on affect during the early months of the COVID-19 pandemic: An ecological momentary assessment study. (September 2021) - Do, Bridgette; Wang, Shirlene D.; Courtney, Jimikaye B.; Dunton, Genevieve F.
Abstract: Engaging in physical activity (PA) may be a promising approach to mitigate the effects of the COVID-19 pandemic and related restrictions on daily affect. The study used ecological momentary assessment (EMA) to examine the within-subject associations of day-level PA with same-day evening affect. Interactions between daily PA and overall stress related to COVID-19 predicting evening affect were also examined. Adults living in the U.S. ( N = 157, M age = 31.7, 84.1% female) participated in a 28-day smartphone-based EMA study during the early months of the pandemic (April–June 2020). Evening EMA surveys assessed daily PA minutes, momentary positive activated and deactivated affect, and momentary negative activated and deactivated affect. An online questionnaire assessed demographics. Multi-level linear regression models assessed day-level associations between PA and evening affect, controlling for age, sex, income, body mass index, employment status, and morning affect. There were N = 2409 person-days in the analysis. Baseline COVID-19 stress was not associated with daily PA minutes ( p = .09) or positive-activated affect ( p = .14), but was associated with lower positive-deactivated affect ( p < .001) and greater negative-activated and negative-deactivated affect ( p s < .001) in the evenings. On days when individuals reported more PA than usual, they reported greater positive-activated and positive-deactivated affect, and lower negative-activated and negative-deactivated affect in the evening ( p s < .001). The interaction of day-level PA and COVID-19 stress predicting evening positive-activated, positive-deactivated, negative-activated, and negative-deactivated affect was not significant ( p s > .05). During the early months of the pandemic, adults experienced improved evening affect on days when they engaged in more PA. However, data did not show that PA counteracts detrimental effects of the COVID-19 pandemic on evening affect. Public health efforts should strategically promote and address barriers to PA during the pandemic. Highlights: Day-level physical activity (PA) predicted greater same-day evening positive affect. Day-level PA predicted lower same-day evening negative affect. Baseline COVID-19 stress was associated with lower positive and greater evening negative affect. Day-level PA did not buffer the association between COVID-19 stress and same-day evening affect.